Tell the truth or not? The Montero mechanism for emissions control at work - Tilman Requate; Eva Camacho-Cuena; Kean Siang Ch'ng; Israel Waichman (Kiel University, Department of Economics, 2018)
We experimentally test the truth-telling mechanism proposed by Montero (2008) for eliciting firms' abatement costs. We compare this mechanism with two well-known alternative allocation mechanisms, grandfathering and pure auctioning. We conducted 27 treatments with a total of 623 participants, controlling for the allocation mechanism, the number of firms, and the true maximal emission levels. We find that, in line with the theoretical predictions, firms over-report their maximal emissions under grandfathering and under-report them under pure auctioning, while under Montero's mechanism firms almost always report their maximal emissions truthfully. However, in terms of efficiency, the difference between Montero's mechanism and pure auctioning disappears when there is more than one firm in the market.
Keywords: C92; D44; L51; Q28; 330; mechanism design; environmental policy; permit trading; auctions; experiment